Economic Evaluation of Home Blood Pressure Monitoring With or Without Telephonic Behavioral Self-Management in Patients With Hypertension - Reed, Shelby D. (2009)
BACKGROUND: The Take Control of Your Blood Pressure trial evaluated the effect of a multicomponent telephonic behavioral lifestyle intervention, patient self-monitoring, and both interventions combined compared with usual care on reducing systolic blood pressure during 24 months. The combined intervention led to a significant reduction in systolic blood pressure compared with usual care alone. We examined direct and patient time costs associated with each intervention. METHODS: We conducted a prospective economic evaluation alongside a randomized controlled trial of 636 patients with hypertension participating in each study intervention. Medical costs were estimated using electronic data representing medical services delivered within the health system. Intervention-related costs were derived using information collected during the trial, administrative records, and published unit costs. RESULTS: During 24 months, patients incurred a mean of $6965 (SD, $22,054) in inpatient costs and $8676 (SD, $9368) in outpatient costs, with no significant differences among the intervention groups. With base-case assumptions, intervention costs were estimated at $90 (SD, $2) for home blood pressure monitoring, $345 (SD, $64) for the behavioral intervention ($31 per telephone encounter), and $416 (SD, $93) for the combined intervention. Patient time costs were estimated at $585 (SD, $487) for home monitoring, $55 (SD, $16) for the behavioral intervention, and $741 (SD, $529) for the combined intervention. CONCLUSIONS: Our analysis demonstrated that the interventions are cost-additive to the health care system in the short term and that patients’ time costs are nontrivial.